Crazy thunder road - Izumiya, Shigeru 1948- (Rapid Eye Movies, 2022)
"When the leader of the once-notorious biker gang of Tokyo falls in love with a barmaid and quickly loses his rebellious ideals, the rest of the gang feels betrayed. Especially the reputedly troubled kid Ken revolts against his former friend." [imdb.com]
Original: Japan 1980
Extras: neues Interview mit Gakuryu (Sogo) Ishii, Audiokommentar von Tom Mes, Essay von Jasper Sharp / Postkarten Set
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc